Satellite cell‐specific ablation of Cdon impairs integrin activation, FGF signalling, and muscle regeneration. Issue 4 (27th February 2020) - Bae, Ju‐Hyeon; Hong, Mingi; Jeong, Hyeon‐Ju; Kim, Hyebeen; Lee, Sang‐Jin; Ryu, Dongryeol; Bae, Gyu‐Un; Cho, Sung Chun; Lee, Young‐Sam; Krauss, Robert S.; Kang, Jong‐Sun
Abstract: Background: Perturbation in cell adhesion and growth factor signalling in satellite cells results in decreased muscle regenerative capacity. Cdon (also called Cdo) is a component of cell adhesion complexes implicated in myogenic differentiation, but its role in muscle regeneration remains to be determined. Methods: We generated inducible satellite cell‐specific Cdon ablation in mice by utilizing a conditional Cdon allele and Pax7 CreERT2 . To induce Cdon ablation, mice were intraperitoneally injected with tamoxifen (tmx). Using cardiotoxin‐induced muscle injury, the effect of Cdon depletion on satellite cell function was examined by histochemistry, immunostaining, and 5‐ethynyl‐2'‐deoxyuridine (EdU) incorporation assay. Isolated myofibers or myoblasts were utilized to determine stem cell function and senescence. To determine pathways related to Cdon deletion, injured muscles were subjected to RNA sequencing analysis. Results: Satellite cell‐specific Cdon ablation causes impaired muscle regeneration with fibrosis, likely attributable to decreased proliferation, and senescence, of satellite cells. Cultured Cdon‐depleted myofibers exhibited 32 ± 9.6% of EdU‐positive satellite cells compared with 58 ± 4.4% satellite cells in control myofibers ( P < 0.05). About 32.5 ± 3.7% Cdon‐ablated myoblasts were positive for senescence‐associated β‐galactosidase (SA‐β‐gal) while only 3.6 ± 0.5% of control satellite cells were positive ( P < 0.001). Transcriptome analysis of muscles at post‐injury Day 4 revealed alterations in genes related to mitogen‐activated protein kinase signalling ( P < 8.29 e −5 ) and extracellular matrix ( P < 2.65 e −24 ). Consistent with this, Cdon‐depleted tibialis anterior muscles had reduced phosphorylated extracellular signal‐regulated kinase (p‐ERK) protein levels and expression of ERK targets, such as Fos (0.23‐fold) and Egr1 (0.31‐fold), relative to mock‐treated control muscles ( P < 0.001). Cdon‐depleted myoblasts exhibited impaired ERK activation in response to basic fibroblast growth factor. Cdon ablation resulted in decreased and/or mislocalized integrin β1 activation in satellite cells (weak or mislocalized integrin1 in tmx = 38.7 ± 1.9%, mock = 21.5 ± 6%, P < 0.05), previously linked with reduced fibroblast growth factor (FGF) responsiveness in aged satellite cells. In mechanistic studies, Cdon interacted with and regulated cell surface localization of FGFR1 and FGFR4, likely contributing to FGF responsiveness of satellite cells. Satellite cells from a progeria model, Zmpste24 −/− myofibers, showed decreased Cdon levels (Cdon‐positive cells in Zmpste24 −/− = 63.3 ± 11%, wild type = 90 ± 7.7%, P < 0.05) and integrin β1 activation (weak or mislocalized integrin β1 in Zmpste24 −/− = 64 ± 6.9%, wild type = 17.4 ± 5.9%, P < 0.01). Conclusions: Cdon deficiency in satellite cells causes impaired proliferation of satellite cells and muscle regeneration via aberrant integrin and FGFR signalling.